GENETIC STUDIES OF FIBRE YIELD RELATED TRAITS AND DAYS TO ANTHESIS IN SOME KENAF (HIBISCUS CANNABINUS L.) ACCESSIONS - Adeyinka, Olawale Samuel; Balogun, Oluwatoyin Morufat (Journal of Agricultural Sciences (Belgrade), 2019)
Kenaf (Hibiscus cannabinus L.) is a multi-purpose economically important natural fibre crop with several industrial applications. However, its potentials have not been fully maximized due to poor yield and its narrow genetic base which limited the available hybrids. The low yield is attributed to highly photoperiod sensitivity of most kenaf accessions because it reduces the vegetative growth. This study attempts to understand the genetic architecture of days to anthesis of kenaf towards the development of photo-insensitive kenaf hybrid. Two early maturing Nigeria kenaf accessions; NHC (12)1 and NHC (3)2 and two late maturing (NHC (9)2 and NHC 15) were crossed to generate F1 population. The F1 hybrid together with parents and its reciprocals were planted in a Randomized Complete Block experiment design with three replicates. Data were collected on days to anthesis (DTA), plant height (HAH), basal stem girth (GAH), base diameter (BDAH) and weight at harvest (WAH) for analysis. The means squares were significant for DTA, HAH, DBAH, GAH and WAH and highest broad sense heritability was observed in DTA (0.98). The GCA: SCA ratio for DTA and BDAH signifies that effect of non-additive genes was prevalent because it is less than a unity while additive gene action was predominant in HAH. The negative GCA estimates for NHC (12)1 and NHC (9)2 indicated a poor combining ability. Only NHC (3)2 x NHC (9)2 shows good specific combining ability (-5.75, 0.33, 0.85, 91.46) for DTA, GAH, BDAH and WAH respectively. NHC (12)1 x NHC (9)2, NHC (3)2 x NHC (9)2, NHC (3)2 x NHC 15, NHC (9)2 x 3NHC (3)2, NHC (9)2 x NHC 15, NHC 15 x NHC (3)2, NHC 15 x NHC (9)2 showed negative significant percent F1 heterosis above mid-parent in days to anthesis and could be employed to breed photo-insensitive early maturing kenaf.